1995
DOI: 10.1097/00000658-199504000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Duodenum-Preserving Resection of the Head of the Pancreas in Chronic Pancreatitis A Prospective, Randomized Trial

Abstract: ObjectiveTwo techniques of duodenum-preserving resection of the head of the pancreas were compared in a prospective, randomized trial. The technical feasibility and effects on quality of life were assessed. Summary Background DataDrainage and resection are the principles of surgery in chronic pancreatitis. The techniques of duodenum-preserving resection of the head of the pancreas as described by Beger and Frey combine both to different degrees. The efficacy of both procedures has not been compared thus far. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
182
0
23

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(211 citation statements)
references
References 25 publications
6
182
0
23
Order By: Relevance
“…Consensus Levels of Agreement: A+ 67.3%; A 24.5%; A− 6.1%; D− 2%; D 0%; D+ 0% Some RCTs have analyzed the results of the mixed procedures. Two RCTs [284,285] compared LR-LPJ vs. DPHR and showed similar short-term and long-term results for pain relief, pancreatic function, mortality rates and quality of life. LR-LPJ is technically easier to perform than DPHR because it does not require the section of the neck of the pancreas [286].…”
Section: S10mentioning
confidence: 92%
See 1 more Smart Citation
“…Consensus Levels of Agreement: A+ 67.3%; A 24.5%; A− 6.1%; D− 2%; D 0%; D+ 0% Some RCTs have analyzed the results of the mixed procedures. Two RCTs [284,285] compared LR-LPJ vs. DPHR and showed similar short-term and long-term results for pain relief, pancreatic function, mortality rates and quality of life. LR-LPJ is technically easier to perform than DPHR because it does not require the section of the neck of the pancreas [286].…”
Section: S10mentioning
confidence: 92%
“…However, LPJ has not been evaluated in RCTs, even if it is widely used. A recent meta-analysis [283], some RCTs [228,232,284] and a recent review [266] have demonstrated the effectiveness of such procedures. DPHR, LR-LPJ and Berne operation are indicated when an inflammatory enlargement of the pancreatic head has been found with or without dilation of the ductal system.…”
Section: S7mentioning
confidence: 99%
“…Endocrine and exocrine functions of the pancreas were not different between the two groups. There was a tendency for lower overall morbidity for Frey procedure (Frey: 9-22% vs Beger: 20-32%, respectively) [16,40]. Although long-term results seem to indicate that both approaches might be equally effective [52], neither procedure can be favoured over the other based on the current report..…”
Section: Resectional Proceduresmentioning
confidence: 62%
“…Comparing Beger procedure with Frey procedure (RCT) [16,40,52], the pain relief (ranging between 93% and 95%), control of complications to adjacent organs (91% Frey, 92% Beger) and improvement in the QOL (58-67% increase in the overall QOL index) were similar. Endocrine and exocrine functions of the pancreas were not different between the two groups.…”
Section: Resectional Proceduresmentioning
confidence: 99%
See 1 more Smart Citation